IMPLEMENTASI VIRTUAL PRIVATE NETWORK MENGGUNAKAN SSTP UNTUK KEAMANAN AKSES KE NETWORK ATTACHED STORAGE SERVER - Novianto, Dian; Japriadi, Yohanes Setiawan; Tommy, Lukas; Sujono, Sujono (JUSIM (Jurnal Sistem Informasi Musirawas), 2025)
Ensuring the integrity of access to Network Attached Storage (NAS) Servers constitutes a significant concern in the context of implementing centralized storage within an organization's business processes. Data leakage problems can arise in the absence of adequate Server access security measures. One solution that can be applied to this problem is the use of a Virtual Private Network (VPN) with the Secure Socket Tunneling Protocol (SSTP) protocol. The SSTP (Secure Sockets Layer/Transport Layer Security) protocol utilizes encryption techniques based on SSL/TLS, thereby enhancing the security of data transmitted over public networks. The system development method employed in this study is PPDIOO, which comprises the preparation, planning, design, implementation, operation, and optimization stages. The present study utilizes TrueNas Core as the software to operate the NAS Server, and MikroTik Routerboard RB951-2HND as the router that will function as a VPN Server. The experimental results demonstrate that SSTP is capable of establishing a secure and encrypted connection, as well as enhancing access control to the NAS. The implementation of SSTP VPN by organizations ensures that only authenticated users can access the NAS, thereby reducing the risk of data leakage and cyberattacks.